Digging up Neandertals at Mujina Pećina? A Mousterian cave site in Croatia - Janković, Ivor (Array, 2007)
The article brings a summary of the interpretation of the archaeological findings from the Mousterian Cave site of Mujina Pećina in Dalmatia, Croatia.